Communicative Approach As A Method For Implementing Emotional Impact When Learning To Communicate In A Foreign Language - Khamidova Nigina Zakirdjonovna (Research Parks Publishing LLC, 2021)
The article analyzes the main directions of the communicative approach in teaching the foreign languages.A special place is occupied by questions about the theoretical prerequisites of this direction, since the systematization of knowledge about a particular methodological direction requires its correlation with the basic sciences for the methodology - linguistics and psychology, that is, consideration of linguistic, psychological theories, concepts that had the greatest impact on him. Consideration of the above characteristics confirms the specificity and novelty of the communicative approach using the emotional factor in comparison with previous methods, and makes us assume that traditional textbooks do not correspond to the goals of communicative learning